The structure and liminesence properties of sodium tellurite glasses doped with Yb2O3 - 383654 Ain Zalikha Mohd. Yusof; Rosli Hussin, supervisor; Fakulti Sains
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2007